2023
DOI: 10.3390/jcm12062231
|View full text |Cite
|
Sign up to set email alerts
|

Adropin Predicts Chronic Kidney Disease in Type 2 Diabetes Mellitus Patients with Chronic Heart Failure

Abstract: Adropin is a multifunctional secreted protein, which is involved in the metabolic modulation of the heart-brain-kidney axis in heart failure (HF). The aim of the study was to detect the plausible predictive value of serum levels of adropin for chronic kidney disease (CKD) grades 1–3 in type 2 diabetes mellitus (T2DM) patients with chronic HF. We enrolled 417 T2DM individuals with chronic HF and subdivided them into two groups depending on the presence of CKD. The control group was composed of 25 healthy indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In addition, Berezina et al. 34 reported that low serum levels of adropin (<2.30 ng/ml) predicted CKD progression in patients with T2DM and concomitant HF treated with dapagliflozin. The results of included trials are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, Berezina et al. 34 reported that low serum levels of adropin (<2.30 ng/ml) predicted CKD progression in patients with T2DM and concomitant HF treated with dapagliflozin. The results of included trials are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, SGLT2 inhibitors demonstrated their ability to reduce the levels of hepcidin, inflammatory cytokines, such as IL-6, TNF-alpha, CRP and markers of kidney injury, as well as increase the levels of hemoglobin, erythropoietin, serum uric acid, adropin, irisin, and apelin. 19,22,28,34,4448 The majority of these studies did not report any correlations between changes in the biomarkers of glomerular/tubular injury, altered glucose and lipid metabolism, adipocyte/skeletal muscle cell dysfunction and changes in UACR, whereas benefits in their changes were closely associated with slower decline in eGFR, for instance in the CREDENCE and DAPA-CKD trials. 19,28 Moreover, SGLT2 inhibitors seem to show improving kidney function independently of their glycemic effects, 49 while they are able to reduce tubular cell glucotoxicity via inhibition of sodium transporters, modulating mitochondrial dysfunction and suppressing local and systemic inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations